Modalities of consumer’s protection at consumer’s lending in European Union Member States are provided with a special directive of the European Parliament and the Council (Directive 2008/48/EZ of the consumer credit agreements). Although this area has bee - Dukic Mijatovic, Marijana; Gongeta, Sanja (European Scientific Journal, ESJ, 2014)
Modalities of consumer’s protection at consumer’s lending in European Union Member States are provided with a special directive of the European Parliament and the Council (Directive 2008/48/EZ of the consumer credit agreements). Although this area has been regulated in European Union by the directives since 1987 (Directive 87/102/EEC), for the economic crisis it was increasingly coming to the fore that the consumer, as a weaker agreement party, was not protected enough. The directive 2008/48/EC on consumer credit is based on the principle of maximum harmonization and regulates the minimum legislative framework for each of the member states. Republic of Croatia has become a member of the European Union. As the youngest of the Member States, Republic of Croatia was obliged to adjust its national legislation concerning the protection of consumers when signing a credit agreement with acquis communautaire, following is the Republic of Serbia on its European path, therefore Directive 2008/48/EZ about consumer purchase credit is being analyzed in this paper, as well as Serbian and Croatian legal regulations in this field.